Problems and solutions in middle size robot soccer: a review - Monteiro, Sérgio (2001)
A review of current scientific and technological problems encountered in building and programming middle size soccer robots is made in this paper. Solutions and solution trends to the problems, as presented by different teams, are also examined. Perceptual systems of individual robots, in particular with respect to object location, communications between robot players, decision making with regard to game strategy and behaviour generation, and, finally, actuation, are the topics dealt with. This makes for a wide perspective on the actual state of the art of middle size soccer robots.